2000
DOI: 10.1006/mthe.2000.0038
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Anti-CCR5 Ribozyme-Transduced CD34+ Hematopoietic Progenitor Cells in Vitro and in a SCID-hu Mouse Model in Vivo

Abstract: The cellular entry of HIV is mediated by the specific interaction of viral envelope glycoproteins with the cell-surface marker CD4 and a chemokine receptor (CCR5 or CXCR4). Individuals with a 32-base-pair (bp) deletion in the CCR5 coding region, which results in a truncated peptide, show resistance to HIV-1 infection. This suggests that the downregulation of CCR5 expression on target cells may prevent HIV infection. Therefore, ribozymes that inhibit the CCR5 expression offer a novel approach for anti-HIV gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
83
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 59 publications
0
83
0
Order By: Relevance
“…40,41,[51][52][53] An alternative therapeutic method for disrupting HIV entry is the use of gene delivery to provide a genetic means to alter expression or block the function of chemokine receptors, for example, intrabodies, ribozymes, intrakines, zinc-fingers or RNAi. [13][14][15][16]54 Our approach to disrupting CCR5 expression on the cell surface relies on cellular expression of a humanized intrabody targeting CCR5. 16 The CCR5 intrabody recog- …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41,[51][52][53] An alternative therapeutic method for disrupting HIV entry is the use of gene delivery to provide a genetic means to alter expression or block the function of chemokine receptors, for example, intrabodies, ribozymes, intrakines, zinc-fingers or RNAi. [13][14][15][16]54 Our approach to disrupting CCR5 expression on the cell surface relies on cellular expression of a humanized intrabody targeting CCR5. 16 The CCR5 intrabody recog- …”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] However, these viral entry disruption strategies have shown varying levels of protection when the viral challenge dose is increased, thus providing the caution that therapeutic efficacy may be breached by high viral loads. [17][18][19] Recent studies have indicated that HIV-1 may be more effectively transmitted during antigen presentation between CD4 + T cells and HIV-1 exposed or infected dendritic cells (DCs), termed an infectious immunological synapse, thus providing a means for increased local viral levels.…”
Section: Introductionmentioning
confidence: 99%
“…So far, intracellular antibodies against viral proteins, 1 anti-human immunodeficiency virus Type 1 (HIV-1) ribozymes, [2][3][4][5] RNA decoys, 6 transdominant viral genes, 7,8 antisense and short interfering RNA (siRNA) against viral and essential cellular proteins for HIV-1 replication [9][10][11][12][13][14] have been used as therapeutic constructs. However, the inhibitory effects on HIV-1 replication by anti-HIV-1 ribozymes, decoys or antisense constructs are generally mild.…”
Section: Introductionmentioning
confidence: 99%
“…So far, a number of promising intracellular immunization strategies have been employed using different molecules that act by a variety of mechanisms such as ribozymes, antisense constructs and siRNAs. [3][4][5][6][7][8] Of these, siRNA-based constructs have received considerable attention due to their target specificity and improved potency. siRNAs use the endogenous RNAi pathway for target recognition and gene silencing.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7]20,[22][23][24][25][26][27]29 Both synthetic siRNAs delivered via transfection and endogenously expressed siRNAs via viral vectors have been employed. Although marked downregulation of CCR5 expression has been observed, complete silencing of coreceptor expression has yet to be achieved.…”
Section: Introductionmentioning
confidence: 99%